2015
DOI: 10.1021/ie503696x
|View full text |Cite
|
Sign up to set email alerts
|

Design and Operation Strategy of CO2 Terminal

Abstract: With recent advancements in the carbon capture and storage (CCS), much interest has been developed in the CO 2 transport options. An infrastructure including pipelines, ships, tanker truck, and railways will be collectively required for a large scale CO 2 transport network. In particular, ship transportation can play a special role in the early phase of CCS infrastructure development as it offers flexible routes between source and offshore storage sites. This work is focused on the design and operational strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…For liquefaction of CO2, various processes have been studied [29,30]. Seo et al [23] investigated four prominent liquefaction systems and concluded that a pre-cooled Linde-…”
Section: Co2 Liquefaction Processmentioning
confidence: 99%